Healthy eating and exercise relationship in female footballers - Bekir Çar; Ahmet Kurtoğlu; Gizem Başkaya (Physical Education of Students)
Background and Study Aim. As a result of the recognition of women's football in the world and the growing popularity of female footballers, the healthy eating of female footballers and their status towards exercise have also become a major research topic. The aim of this study is to investigate the attitudes of female soccer players towards healthy eating and their sports addiction. This study aimed to assess female footballers' attitudes toward healthy eating and exercise addiction based on age, league, position, active sports year, training status and number of exercises per week, and examine female football players' attitudes toward healthy eating and exercise addiction.